EFFORTS TO IMPROVE EMPLOYEE PERFORMANCE THROUGH TRAINING, CAREER DEVELOPMENT, AND TEAMWORK - Muhammad Ivankhan Firjatullah; Supardjo Supardjo; Sukardi Sukardi; Hasyim Hasyim (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study aims to analyze the influence of training, career development, and teamwork on employee performance at KSPPS Nusa Indah. This study uses a quantitative approach with data collected through a Likert-scale questionnaire. The population consists of all employees, and a saturated sampling technique is applied so that all members of the population participate as respondents. Data analysis was conducted using multiple linear regression with the help of SPSS. The results show that training and career development have a positive influence on employee performance, with career development emerging as the most dominant factor. Meanwhile, teamwork shows a positive relationship with employee performance but does not show a significant influence. Overall, these three variables contribute to explaining variations in employee performance. Based on these findings, this study recommends that organizations improve the quality of competency-based training programs and establish a clearer and more structured career development system to strengthen employee motivation and improve overall performance. Keywords: Training; Career Development; Teamwork; Employee Performance